Examining student burnout causes among English as a foreign language students: focus on school climate and student growth mindset - Liu, Xiaoling (Frontiers in Psychology, 2023)
The aim of this study was to examine the relationship between student burnout and two key factors: perceived school climate and growth mindset, in the context of English as a foreign language (EFL) learning among Chinese students. A sample of 412 intermediate English language learners from China participated in an online survey and responded to valid measures of the three constructs. The validity of the scales used to measure the three latent variables was established through the use of confirmatory factor analysis (CFA). Structural equation modeling (SEM) was then used to test the proposed model. The results of SEM showed that both perceived school climate and growth mindset had a significant positive impact on EFL student burnout, with perceived school climate having a stronger effect compared to growth mindset. These findings suggest that promoting a positive school climate and fostering a student growth mindset can help reduce student burnout in EFL settings.